2020
DOI: 10.26848/rbgf.v13.2.p595-612
|View full text |Cite
|
Sign up to set email alerts
|

Identificação de Fragmentos Florestais Potencias para a delimitação de Corredores Ecológicos na bacia hidrográfica do Rio Itapemirim, ES por meio técnicas de Sensoriamento Remoto

Abstract: Os corredores ecológicos surgem como alternativa para mitigar os efeitos da fragmentação florestal permitindo entre eles o fluxo gênico de fauna e flora e a recolonização de áreas degradadas. Diante do exposto o presente estudo teve como objetivo, identificar para a bacia hidrográfica do rio Itapemirim, ES, por meio de metodologia desenvolvida em Sistemas de Informações Geográficas, a delimitação de corredores ecológicos que propiciem a interligação de fragmentos florestais, identificados mediante análise das … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 7 publications
1
6
0
5
Order By: Relevance
“…This concentration of fragments in less complex shapes is evident in the dispersion analysis (Figure 3B). Jesus et al (2015), Rusca et al (2017), Rex et al (2018) and Thiago et al (2020) found similar results in the shape/area relationship of the fragments when studying urban and periurban basins. NUMP: number of patches; CA: class area; ZLAND: occupancy percentage.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…This concentration of fragments in less complex shapes is evident in the dispersion analysis (Figure 3B). Jesus et al (2015), Rusca et al (2017), Rex et al (2018) and Thiago et al (2020) found similar results in the shape/area relationship of the fragments when studying urban and periurban basins. NUMP: number of patches; CA: class area; ZLAND: occupancy percentage.…”
Section: Resultssupporting
confidence: 52%
“…This diagnosis converges with the studies by Numata and Cochrane (2012), Haddad et al (2015) and Hansen et al (2020), whose data showed an increase in the number of fragments < 10 ha in Amazonian forests, where there is a numerical predominance of patches smaller than 100 ha. Concerning hydrographic basins as a territorial unit, several studies have found similar results, both in the Amazon and in other biomes (Jesus et al, 2015;Rusca et al, 2017;Rex et al, 2018;Lisboa et al, 2019;Andrade et al, 2020;Cavalcante et al, 2020;Castro et al, 2020;Thiago et al, 2020).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Aliar essa evolução à conservação ambiental se torna um grande desafio, uma vez que se torna evidente a intensificação dos impactos sobre o meio ambiente e sua biodiversidade, principalmente em relação aos recursos hídricos e o uso do solo (Nascimento et al, 2016). Essa falta de planejamento em relação ao uso e ocupação do solo é um fator agravador do processo de fragmentação florestal de um ambiente (Magalhães et al, 2020).…”
Section: Introductionunclassified